REPOSISI INTELIJEN NEGARA DALAM BADAN INTELIJEN NEGARA PASCA UNDANG-UNDANG NOMOR 17 TAHUN 2011 TENTANG INTELIJEN NEGARA - Fitri Atur Arum (Universitas Janabadra, 2019)
ABSTRACT Intelligence is essentially a matter relating to the information needed not as an objective, but as material or instruments for decision making. Intelligence can be seen as the process of gathering and processing information, information as a product, and the organization that handles it. Therefore the main intelligence activity is gathering and searching for information, evaluating information, integrating, analyzing, concluding, and estimating the dynamics of national security using scientific methods. The function of state intelligence within the framework of intelligence reform in a democratic rule of law is carried out by various government agencies or non-ministerial government institutions in accordance with their respective main tasks. In terms of repositioning the state intelligence can be highlighted in terms of the implementation of the coordination of State Intelligence, BIN has a coordinative relationship with the Regional BIN (Binda). The coordination between BIN and Binda is coordinative which is carried out every day in relation to the nine strategic components. In the case of intelligence operations, BIN did not coordinate with Binda because Binda was